Teaching English for Children at Budi Mulia Orphanage with Interactive Games - Flashcard - Yanuarius Seran; Thresia T. Semiun; Fransiska Densiana Luruk; Delti Yulita; Jose Da Conceicao Verdial; Edmundus Bouk; Antonio Constantino Soares; Maria Fridolin Naben; Maria Wihelmina Wisrance; Petrus Banfoe (Jurnal Pengabdian Sains dan Humaniora, 2026)
The urgency of this community service lies in the persistent difficulties faced by children in comprehending English, particularly in mastering vocabulary. Therefore, the objective of this community service was to teach children with interactive and interesting games and provide vocabulary mastery. The method used in this activity was interactive games – flashcard. Vocabulary test was given at every meeting to evaluate participants’ vocabulary mastery. The result of this activity showed that the participants were very enthusiastic and they fully took part and in every session of this activity. They obtained more new vocabulary and learned pronunciation of plenty of new vocabulary.  The average score of the first meeting was 42% for transportation vocabulary and 58% for body part vocabulary. On the second day, the average score was 24% for vegetables vocabulary and 46% for tools for eating and drinking. The score improved on the third day where 94% for transportation, 96% for body part, 100% for vegetables, and 98% for tools for eating and drinking. The score also got significantly improved on the fourth day where 94% for transportation, 98% for body part, 100% for vegetables, and 98% for tools for eating and drinking. The fifth meeting created a good result where participants score was 91% on average. This overall result proved that participants obtained significant vocabulary achievement.